Market selection process of born-globals - Häkli, Markus (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
Key elements of this study are to understand born-globals and the market selection decision process. The goal is to go beyond the traditional born-global theory and add the international market selection theory to it. The additional layer to the born-global market selection theory should include market selection tools and a market selection decision framework. This is an ethnographic case study with the focus on Funzi’s market selection process. Funzi is a born-global start-up founded in 2014 and provides free learning to its users across the globe. Course provided by Funzi are built around the themes of livelihood and well-being. The primary markets for the case company are in Africa, but the company has had users from 194 countries since inception. In general, the company focuses on emerging markets as there is a need for the product. The theoretical background of this study includes two main theories. The theory of born-globals investigates the different factors affecting internationalization such as business networks and limited home market. The international market selection theory adds a systematic decision framework for market selection and reviews tools available for market selection. At the end of the theory section a synthesis of the theory is provided in addition to a market selection process for born-globals figure. The study is based on qualitative data gathered via interviews, company documents and personal notes. The main findings of this study support the previous literature on born-globals and their internationalization. Factors such as a limited home market, business networks and social ties, international orientation and prior experience of the founders, and dynamics of the industry are key in the internationalization of born-globals. The findings also state that the case company systematically analyzes markets prior to entry thus providing evidence to further study how the international market selection theory can provide new insights into born-globals and their market selection process. In the theoretical contribution chapter an updated figure of the market selection process of born-globals is provided. This figure may be used by managers of born-globals as a method to create a more systematic market selection process.